Exemplification in news narratives: stigmatizing and securitizing effects - Sellnow-Richmond, Deborah D.; Lukacovic, Marta N.; Sellnow-Richmond, Scott A. (Frontiers in Communication, 2024)
Exemplification, the use of emotionally evocative messages to elicit a response based on impression formation, are frequently present in news messages. The present study examined the use of positive vs. negative exemplars in news stories to determine the role of stigmatization and securitization in these messages and whether this impacts perceptions of the importance and quality of news. This study tested exemplification's effects using three conditions: positive, negative, and non-exemplar news stories—two valences of exemplification and a control condition. Results indicate that as stigmatized impressions increase, securitization decreases, valence of exemplification predicts perceptions on the quality of news, and valence of exemplification predicts perceptions on the general interest of the issues. Implications suggest news message creators should consider positive exemplars in place of negative exemplars to minimize unintended negative effects.